Factors influencing Digital Banking Service Quality: A comparative study between SBI and HDFC bank in Hyderabad, India - Choudhury, Prasant Kumar; Mishra, Dr. Nihar Ranjan; Zipporah, G (The journal of contemporary issues in business and government, 2022)
Digital banking services in India plays an important role since 5 years as the customers are looking beyond the traditional way of banking. Digital banking Services like Electronic Fund Transfer(NEFT,RTGS,IMPS), UPI, ATM, Cash deposit machine, Mobile Banking Application, Debit Card, Credit Card are growing exponentially since 2017 due to the several initiative by government like incentives for customers and merchants, Demonetization, financial inclusion and for customer and traders own interest and lastly due to Covid-19.This is the reason why most of the commercial banks are trying to introduce various digital banking services which is paperless and does not require branch visit. Now the customer can make round the clock money transfer using NEFT/RTGS due to initiative taken by RBI. Undoubtedly there are many advantages of digital banking, but at the same time, there are challenges to be addressed by the banker is security to the customers with respect to their personal information and money. This study aims at providing insight into the various factors that influence for digital banking service quality and customer perception of services provided by the SBI and HDFC bank in Hyderabad, India.